Reinterpreting the Objectives of Islamic Marriage in the Contemporary Era: A Maqāṣid al-Sharīʿah Perspective on Childfree and Misyar Marriage - Haikal Habibie; Mawaddah; Taupik Kurrahman; Nasywa Azzahra (Mir'ah: Family Law and Legal Culture, 2025)
This study examines the phenomena of childfree marriage and misyar marriage from the perspective of maqāṣid ash-sharīʿah, as an effort to reinterpret the objectives of Islamic marriage in the contemporary era. This research employs a normative legal method with qualitative, conceptual, and normative-theological approaches through an examination of the Qur’an, hadith, scholarly opinions, and contemporary Islamic family law literature. The findings indicate that childfree marriage and misyar marriage cannot be assessed absolutely, but must be examined based on intention, underlying reasons, mechanisms, impacts, and their conformity with the objectives of Islamic law. Temporary childfree decisions may be permissible when grounded in maslahah, such as health considerations, psychological readiness, or family stability. However, permanent childfree decisions without urgent justification may conflict with hifz al-nasl. Misyar marriage may be formally valid if it fulfills the essential pillars and conditions of marriage; however, from a maqāṣid perspective, it is acceptable only in a limited sense when it does not eliminate the wife’s basic rights, cause exploitation, and continues to uphold justice and legal protection. The contribution of this study lies in its integrative analysis of childfree marriage and misyar marriage within the framework of maqāṣid ash-sharīʿah. The limitation of this research is that it remains a normative library-based study and has not yet employed empirical data from practitioners or related institutions.